2019
DOI: 10.1039/c9tc00299e
|View full text |Cite
|
Sign up to set email alerts
|

SiCxNy:Fe films as a tunable ferromagnetic material with tailored conductivity

Abstract: Ferromagnetic SiCxNy:Fe films with tunable functional properties were synthesized, providing a novel material for spintronics applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Moreover, as shown in Figure 3(e), the Fouriertransformed extended X-ray absorption fine structure (FT-EXAFS) spectra show that Fe-N-C-Si, Fe-N-C and FePc display similar peaks at ~1.45 Å, and have no peak at ~2.2 Å, proving the atomic dispersion of Fe atoms in Fe-N-C-Si and Fe-N-C. Besides, for Fe-N-C-Si, no peak corresponding to Fe-Si bonds (> 2 Å) is observed in the FE-EXAFS spectra [45][46][47], manifesting that Si is bonded to C/N atoms, rather than Fe atoms in Fe-N-C-Si, consistent with the XPS results. In addition, the wavelet transform (WT)-EXAFS contour plot of Fe foil exhibits an intensity maximum at about 8.5 Å −1 (Figure 3(f)), which is attributed to the Fe-Fe signal.…”
Section: Structural and Morphology Characterizations Of Catalystsmentioning
confidence: 90%
“…Moreover, as shown in Figure 3(e), the Fouriertransformed extended X-ray absorption fine structure (FT-EXAFS) spectra show that Fe-N-C-Si, Fe-N-C and FePc display similar peaks at ~1.45 Å, and have no peak at ~2.2 Å, proving the atomic dispersion of Fe atoms in Fe-N-C-Si and Fe-N-C. Besides, for Fe-N-C-Si, no peak corresponding to Fe-Si bonds (> 2 Å) is observed in the FE-EXAFS spectra [45][46][47], manifesting that Si is bonded to C/N atoms, rather than Fe atoms in Fe-N-C-Si, consistent with the XPS results. In addition, the wavelet transform (WT)-EXAFS contour plot of Fe foil exhibits an intensity maximum at about 8.5 Å −1 (Figure 3(f)), which is attributed to the Fe-Fe signal.…”
Section: Structural and Morphology Characterizations Of Catalystsmentioning
confidence: 90%
“…The magnetic hyperfine structure of bcc-Fe may not be observed at room temperature due to superparamagnetic relaxation resulting in the collapse magnetically ordered pattern (sextet) into a single absorption line [43]. The formation of α-Fe nanoparticles in SiCNFe ceramics was reported in numerous publications [23][24][25][26][27][28][29][30][31][32][33]36] and this is expected for SiCNFe annealed at 1100 • C. The EPR spectra of these samples belonging to α-Fe nanoparticles were discussed by Misra et al [28] and splitting of the W-band EPR spectra were observed [29]. Clear evidence of the formation of both α-Fe nanoparticles and large α-Fe clusters was obtained recently by Stepina et al [32] in granulated SiCNFe films with high Fe concentration.…”
Section: Component IVmentioning
confidence: 99%
“…The SiCN/Fe ceramic material was investigated intensively [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] and it was found that the magnetism of this material is a sum of different sources of magnetism: ferromagnetic nanoparticles with different compositions, superparamagnetic Fe 3+ ion clusters and paramagnetic Fe 3+ ions. Hence, one of very important aim to carefully control the chemical composition of SiCNFe ceramics with predictable magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation